A nationwide study of blood transfusion in hip fracture patients: linked analysis from the Scottish Hip Fracture Audit and the Scottish National Blood Transfusion Service. (1st November 2022) - Farrow, Luke; Brasnic, Lorena; Martin, Caroline; Ward, Kirsty; Adam, Karen; Hall, Andrew J.; Clement, Nick D.; MacLullich, Alasdair M. J.
Abstract : Aims: The aim of this study was to examine perioperative blood transfusion practice, and associations with clinical outcomes, in a national cohort of hip fracture patients. Methods: A retrospective cohort study was undertaken using linked data from the Scottish Hip Fracture Audit and the Scottish National Blood Transfusion Service between May 2016 and December 2020. All patients aged ≥ 50 years admitted to a Scottish hospital with a hip fracture were included. Assessment of the factors independently associated with red blood cell transfusion (RBCT) during admission was performed, alongside determination of the association between RBCT and hip fracture outcomes. Results: A total of 23, 266 individual patient records from 18 hospitals were included. The overall rate of blood transfusion during admission was 28.7% (n = 6, 685). There was inter-hospital variation in transfusion rate, ranging from 16.6% to 37.4%. Independent perioperative factors significantly associated with RBCT included older age (90 to 94 years, odds ratio (OR) 3.04 (95% confidence interval (CI) 2.28 to 4.04); p < 0.001), intramedullary fixation (OR 7.15 (95% CI 6.50 to 7.86); p < 0.001), and sliding hip screw constructs (OR 2.34 (95% CI 2.19 to 2.50); p < 0.001). Blood transfusion during admission was significantly associated with higher rates of 30-day mortality (OR 1.35 (95% CI 1.19 to 1.53); p < 0.001) and 60-day mortality (OR 1.54 (95% CI 1.43 to 1.67); p < 0.001), as well as delays to postoperative mobilization, higher likelihood of not returning to their home, and longer length of stay. Conclusion: Blood transfusion after hip fracture was common, although practice varied nationally. RBCT is associated with adverse outcomes, which is most likely a reflection of perioperative anaemia, rather than any causal effect. Use of RBCT does not appear to reverse this effect, highlighting the importance of perioperative blood loss reduction. Cite this article: Bone Joint J 2022;104-B(11):1266–1272.